Effects of surface texture on flow in channels - Lim, Sherman Zheng Rui (2017)
Friction is a resistive force experienced in everyday activities due to the relative motion of two matters. It can be favorable or disadvantageous depending on the application. In many engineering applications such as fluid flow in pipes, friction is proven to be disadvantageous due to the loss of energy and thus a reduction in efficiency. As a result, many studies have been done to reduce the frictional drag experienced when fluid flows through pipes. By altering the surface structure appropriately, the interaction between the fluid and solid surface can be modified such that the adhesion is decreased which reduces the frictional drag experienced.